(untitled) (Journal of the College of Basic Education, 2024)
Jalawla region is located in the northeastern part of Iraq within Diyala Governorate. The geological formations of the region were studied and found to be of recent formation, dating back to Quaternary deposits. The formation consists of layers of sandstone and clay, and this disparity in the layers leads to active water and wind erosion processes. The study showed that climate elements are one of the main factors in determining the size of infrastructure capacity. Hydro and wind in the region. The soil texture in the region also varies spatially, ranging from mixture to clayey texture. Through the study and morphometric analysis of water and wind erosion in the Jalawla area, it was found that water erosion is one of the most important factors influencing the formation of the general geomorphological appearance of the surface of the region, and it is also more influential than wind erosion in stripping and sweeping away the soil. The volume of water erosion according to the Duclas equation reached about (3.27 m3/km2/year), and this value is considered above average, and the gully erosion reached (1842.4 m3/km2), which is high erosion according to the Bergsma equation. While the potential capacity of the winds reached (43.44) degrees, which is moderate erosion according to the limits set by the Chepil equation. The study concluded that the region is exposed to water and wind erosion to varying degrees, which leave environmental and economic impacts, which necessitate taking measures to reduce them.